Law reports of the Commonwealth : commercial law reports (Butterworths LondonGB, 1980)
Contains cases dealing with general topics such as banking law, insurance, shipping, contract, arbitration, trademarks, patents and copyrights, and company law. Cases are in chronological order and cover jurisdictions from regions of the Commonwealth.\n Includes alphabetical list of cases reported, cases,\n constitutions, legislation and other sources referred\n to, and a subject matter index
Library has 1980-84; '85; '86; '87; '88; '89; '90